Influência da transposição de bacias do Paraíba do Sul-Piraí-Guandu na descarga de sólidos suspensos para a Baía de Sepetiba - Jordão, Marcelo Di Lello (2017)
In this thesis, a study on the morphological responses and wash load discharge from the Guandu River due to the Para´ıba do Sul-Pira´ı-Guandu basins transposition is presented. The first part described the morphological evolution of the Guandu River and its delta. The methodology applied in this part involved field visits and the construction of a cartographic collection, images and reports. The Guandu basin had seven different configurations between 1729 and 2010. The abrupt increase in flow due to transposition resulted in the downstream erosion, the decreased of its slope and the increase in the mean depth. This erosion sustained the rapid growth of the delta. The second part described the impact of transposition in terms of the annual wash load discharge. The wash load discharge estimation was obtained from the monitoring of 11 stations installed along the transposition and the Guandu and Guandu Mirim Rivers between the hydrological years of 2014 and 2016. The transposition system trap efficiency was 59% during the dry year and 62% the during typical year. The Lajes and Vigário reservoirs were the main responsible for the suspended sediment retention. The S˜ao Francisco Channel wash load discharge was 26,446±20,761 t to the dry year and 90,337±16,318 t to the typical year. The transposition accounted for about 40% of the annual discharge in the typical year and 71% in the year of dry year. The water treatment plant was responsible for the transposition of 38,687±9,340 t to the typical year and 16,483±13,243 t to the dry year. This study concluded that, nowadays, the Guandu Channel is the main source of suspended sediment to the Sepetiba Bay.